PENGARUH LITERASI AKUNTANSI DAN SAK EMKM TERHADAP KINERJA UMKM DESA SEI BEROMBANG DIMODERASI PEMERINTAH - Muhammad Irfan; Heny Triastuti Kurnianingsih; Zufrizal (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the influence of accounting literacy and the implementation of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) on the financial performance of MSMEs in Sei Berombang Village, Panai Hilir District, with government support serving as a moderating variable. The problem addressed in this study is the relatively low quality of MSME financial management, as indicated by suboptimal financial record-keeping and limited implementation of accounting standards. The population consisted of all MSME owners in Sei Berombang Village, totaling 72 business units, with a sample of 61respondents selected using the simple random sampling technique. Data were analyzed using multiple linear regression analysis and Moderated Regression Analysis (MRA) with the assistance of SPSS software. The results indicate that accounting literacy and the implementation of SAK EMKM have a positive and significant effect on the financial performance of MSMEs. Furthermore, government support strengthens the influence of accounting literacy and the implementation of SAK EMKM on the financial performance of MSMEs in Sei Berombang Village